Atractylodes lancea volatile oils attenuated helicobacter pylori NCTC11637 growth and biofilm. (October 2019) - Yu, Min; Wang, Xiaochun; Ling, Feng; Wang, Hua; Zhang, Ping; Shao, Shihe
Abstract: Atractylodes lancea is a traditional Chinese perennial herb, which has been used for treating gastrointestinal diseases in traditional medicine. The aim of this study was to investigate the effect of Atractylodes lancea volatile oils on the planktonic growth and biofilm formation of Helicobacter pylori ( H. pylori ). Firstly, the minimal inhibitory concentration (MIC) of the volatile oils against H. pylori were determined using broth dilution method. SPSS17.0 was used to account 50% inhibiting concentration (IC50). Moreover, the anti-biofilm activity of the volatile oils was determined by crystal violet measurement and fluorescence microscope. Finally, gastric epithelial cells (GES-1 cells) were co-incubated with H. pylori with or without volatile oils treated. Real-time PCR and western blot were performed to detect the translocation of virulence factor Cag A. We found that Atractylodes lancea volatile oils inhibited the growth of H. pylori in a concentration dependent manner. The MIC and IC50 of volatile oils against H. pylori were 7.5 mg/mL and 2.181 mg/mL respectively. Fluorescence microscopy and crystal violet measurement indicated that volatile oils at sub-MIC concentration could reduce biofilm formation of H. pylori . In addition, volatile oils decreased the translocation of Cag A and reduced inflammatory cytokine IL-8 in GES-1 cells. Our results suggested that Atractylodes lancea volatile oils could be a potential compound of a novel class of H. pylori inhibitors with anti- H. pylori effects. Highlights: Atractylodes lancea volatile oils inhibit the growth of H. pylori NCTC 11637. Sub-MIC concentration of volatile oils reduce the biofilm formation of H. pylori NCTC11637. Volatile oils at sub-MIC concentration decrease the secretion of IL-8 in GES-1 cells in a dose dependent manner. Volatile oils at sub-MIC concentration decrease translocation of H. pylori virulence factor Cag A in GES-1 cells.